1997
DOI: 10.1002/art.1780401010
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of interleukin‐10/interleukin‐12 balance in the regulation of the type 2 T helper cytokine response in reactive arthritis

Abstract: Objective. To investigate whether a predominant type 1 T helper (Thl) or Th2 cytokine pattern is present in the joints of patients with reactive arthritis (ReA), and whether the cytokine pattern can be modulated by cytokines or anticytokines. Methods. Eleven patients with ReA following infection with either Chlamydia trachomatis, Yersinia enterocolitica, or Salmonella enteritidis were investigated for the presence of Th1/Th2 cytokines in the joints. Release of the bacteria‐specific cytokines interferon‐γ (IFNγ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
3

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 153 publications
(76 citation statements)
references
References 50 publications
5
68
0
3
Order By: Relevance
“…Mononuclear cells in synovial fluid have been shown to express high levels of IL-4 and IL-10. Consistent with culture data, more IL-4-expressing cells than IFN␥-expressing cells were observed in the synovial membrane (35).…”
Section: Host-microbe Interactions In Chlamydia-induced Arthritissupporting
confidence: 87%
See 1 more Smart Citation
“…Mononuclear cells in synovial fluid have been shown to express high levels of IL-4 and IL-10. Consistent with culture data, more IL-4-expressing cells than IFN␥-expressing cells were observed in the synovial membrane (35).…”
Section: Host-microbe Interactions In Chlamydia-induced Arthritissupporting
confidence: 87%
“…In ReA, failure of effective bacterial elimination at the initiation of the disease may be attributable to a relative lack of Th1 cytokine production. Several studies have demon- 504 INMAN AND CHIU strated a relative decrease in Th1 cytokines in peripheral blood and synovium of patients with ReA (35,37). In a study of 11 patients with ReA, it was shown that stimulation of synovial fluid mononuclear cells resulted in low levels of IFN␥ and TNF␣ but high amounts of IL-10 (35).…”
Section: Host-microbe Interactions In Chlamydia-induced Arthritismentioning
confidence: 99%
“…A Th1 response is crucial for successfully fighting microbes such as Yersinia and Chlamydia, and their elimination is inhibited by IL-10 (9 -11). We have previously reported that a relative high amount of IL-4 and IL-10 and/or a low secretion of IFN-␥ and TNF-␣ occurs in the joint (5,6) or peripheral blood (42) of ReA patients, suggesting that such an ineffective Th1 response contributes to bacterial persistence. Therefore, the analysis of the cytokine secretion pattern of the TCCs upon stimulation with the immunodominant epitope was of great interest.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of bacterial Ag (2,3) or DNA (4) in the joint suggests that local Ag may drive the immune response. The recent description of a Th2-cytokine secretion pattern in ReA (5)(6)(7)(8) suggests that an ineffective Th1 response may contribute to bacterial persistence in vivo, because Th1 cytokines such as IFN-␥ and TNF-␣ are crucial for the elimination of both Chlamydia (9,10) and Yersinia (11).…”
Section: R Eactive Arthritis (Rea)mentioning
confidence: 99%
See 1 more Smart Citation